Impaired awareness of deficits and neuropsychological functioning following traumatic brain injury, frontotemporal dementia, corticobasal degeneration and progressive supranuclear palsy - O'Keeffe, Fiadhnait (Trinity College (Dublin, Ireland). School of Psychology, 2006)
This dissertation consists of an investigation into the phenomenon of impaired selfawareness of deficits following brain damage. Despite a large interest in the area in the neuropsychological literature, there is a distinct lack of consensus regarding assessment and underlying neuropsychological correlates of impaired awareness. The three studies presented in this thesis attempted to elucidate the neuropsychological correlates of awareness by adopting a multidimensional approach to assessment in individuals with traumatic brain injury (TBI), frontotemporal dementia (FTD), corticobasal degeneration (CBD) and progressive supranuclear palsy (PSP).
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin